2016
DOI: 10.1016/j.physletb.2016.01.044
|View full text |Cite
|
Sign up to set email alerts
|

First measurement of the helicity asymmetry E in photoproduction on the proton

Abstract: Results are presented for the first measurement of the double-polarization helicity asymmetry E for the eta photoproduction reaction gamma p -> eta p. Data were obtained using the FROzen Spin Target (FROST) with the CLAS spectrometer in Hall B at Jefferson Lab, covering a range of center-of-mass energy W from threshold to 2.15 GeV and a large range in center-of-mass polar angle. As an initial application of these data, the results have been incorporated into the Julich-Bonn model to examine the case for the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
5
29
0
Order By: Relevance
“…There is a clear structure slightly below W = 1.7 GeV. However, in the analysis it was found that the structure can be explained as a conventional effect from the interference of a few multipoles, and no new narrow structure is needed for the description of the data [13].…”
Section: Analysis Of η and Kλ Photoproductionmentioning
confidence: 86%
See 2 more Smart Citations
“…There is a clear structure slightly below W = 1.7 GeV. However, in the analysis it was found that the structure can be explained as a conventional effect from the interference of a few multipoles, and no new narrow structure is needed for the description of the data [13].…”
Section: Analysis Of η and Kλ Photoproductionmentioning
confidence: 86%
“…4. The E observable in the reaction γp → ηp has been recently measured by the CLAS collaboration [13] for the first time ever. The different lines correspond to two fits to differently binned data.…”
Section: Analysis Of η and Kλ Photoproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of the structure as narrow resonance was supported by further studies [13][14][15][16], the results reported in [17] were ambiguous. In a study of the helicity asymmetry of the reaction γp → ηp, no evidence for N (1685) was found [18].…”
mentioning
confidence: 99%
“…The new data on E for the reaction γd → ηp(n) in [25] -with a spectator neutron -differ significantly from first BnGa fits which were performed before the data on double-polarization observables on γp → ηp on protons became available [18,26]. To explore this discrepancy, we included the new MAMI data for η production off protons (bound in deuterons) [25] in the fits.…”
mentioning
confidence: 99%